CABI Publications 1 A world dictionary of livestock breeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
A world dictionary, of livestock breeds: types and varieties 4th edition by I L Mason, 1996, 288pp Hbk price UKL40 00 ISBN 0 85199 102 5